Golden Hour Treatment With tPA (Tissue-Type Plasminogen Activator) in the BEST-MSU Study. Issue 2 (24th January 2023) - Mackey, Jason; Yamal, Jose-Miguel; Parker, Stephanie A.; Silnes, Kelly; Rajan, Suja S.; Jacob, Asha P.; Wang, Mengxi; Singh, Noopur; Jones, William J.; Spokoyny, Ilana; Navi, Babak B.; Saver, Jeffrey L.; et al.
Abstract : Background: Treatment of patients with acute ischemic stroke on mobile stroke units (MSUs) improves outcomes compared with management by standard emergency medical services ambulances and is associated with more patients treated with intravenous tPA (tissue-type plasminogen activator) in the first golden hour after last known normal. We explored the predictors and outcomes of first-hour treatment (FHT) compared with later treatment in an alternating-week cluster-controlled trial of MSUs. Methods: We analyzed all patients treated with intravenous tPA in the BEST-MSU Study (Benefits of Stroke Treatment Delivered by a Mobile Stroke Unit Compared to Standard Management by Emergency Medical Services). After stratifying by treatment timeframe, we identified factors associated with FHT. We performed adjusted analyses of the association between FHT and clinical outcome and modeled the shape of the relationship between last known normal–to–treatment time and excellent outcome. Results: Among 941 tPA-treated patients, 206 (21.8%) had lytic started within 60 minutes. Treatment on the MSU, older age, male sex, alert by 911, faster arrival on-scene and imaging, more severe stroke, atrial fibrillation, and absence of heart failure and pretreatment antihypertensive treatment were associated with FHT. Compared with later treatment, FHT was associated with higher adjusted odds ratio for 90-day modified Rankin Scale score of 0 to 1 (odds ratio, 1.87 [95% CI, 1.25–2.84]; P =0.003). Among FHT patients, 68% achieved a 90-day modified Rankin Scale of 0 or 1 or returned to their baseline status. FHT was not associated with higher risk of hemorrhage and was associated with reduced risk of treating neurovascular mimics. Conclusions: FHT almost doubles the odds of excellent clinical outcome without increased risk compared with later treatment, which supports the use of MSUs.